1976
DOI: 10.1007/bf01317869
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of avian infectious bronchitis virus in primary chick kidney cells

Abstract: Primary chick kidney cells were infected with avian infectious bronchitis virus (IBV) and examined by electron microscopy. Virus particles entered the cells by viropexis and distinction could be made between engulfment by cell processes (phagocytosis) and entry by micropinocytosis in coated transport vesicles. Virus maturation occurred by budding into either the cisternae of the endoplasmic reticulum or cytoplasmic vacuoles, and evidence was obtained to suggest that the viral surface projections could be attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 13 publications
0
44
0
Order By: Relevance
“…We have previously shown that p1a-22 is cleaved at a conserved 3CLpro cleavage site at its amino terminus and at its carboxy terminus at a novel noncanonical Q_N 3CLpro cleavage site that is completely conserved among the coronaviruses (27). The masses of the newly detected proteins (10,12, and 15 kDa) correspond precisely with the predicted masses of products obtained if cleavage occurred at consensus 3CLpro cleavage sites. In addition, the gene 1-encoded proteins corresponding to MHV-A59 p1a-10, -12, and -15 have recently been detected in cells infected with human coronavirus 229E, and homologs of p1a-10 and p1a-15 have also been identified in infectious bronchitis virusand MHV-JHM-infected cells, respectively (26,37,47).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously shown that p1a-22 is cleaved at a conserved 3CLpro cleavage site at its amino terminus and at its carboxy terminus at a novel noncanonical Q_N 3CLpro cleavage site that is completely conserved among the coronaviruses (27). The masses of the newly detected proteins (10,12, and 15 kDa) correspond precisely with the predicted masses of products obtained if cleavage occurred at consensus 3CLpro cleavage sites. In addition, the gene 1-encoded proteins corresponding to MHV-A59 p1a-10, -12, and -15 have recently been detected in cells infected with human coronavirus 229E, and homologs of p1a-10 and p1a-15 have also been identified in infectious bronchitis virusand MHV-JHM-infected cells, respectively (26,37,47).…”
Section: Discussionmentioning
confidence: 96%
“…Coronavirus assembly has been shown to occur primarily in the membranes of the rough endoplasmic reticulum and IC, followed by transport to or through the Golgi prior to exocytic release of progeny virions (10,15,21,22,36,(42)(43)(44)(45). Our dual labeling using directly dye-conjugated ␣M in combination with either ␣N or a number of anti-gene 1 antibodies clearly demonstrated that a majority of signal for the gene 1 proteins or N had no overlap with M. Yet, there were areas of intercalation and interface of gene 1 proteins and N with M such that there was a margin of coincident signal at the periphery of sites of M accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, some coronaviruses such as infectious avian bronchitis virus (beaudette strain) have been reported able to get out of the host cells by coated vesicle-mediated exocytosis (Chasey and Alexander, 1976). Previous electron microscopic data suggested that HEV seemed to be released in groups from cultured porcine kidney cells by way of smooth-surfaced vesicles (Clarke and McFerran, 1971).…”
Section: Discussionmentioning
confidence: 98%
“…Early electron microscopic studies demonstrated that coronavirus morphogenesis takes place at intracellular membranes and identified the cisternae of the endoplasmic reticulum as the site of budding of IBV and HCoV-229E (Becker et al, 1967;Chasey and Alexander, 1976;Hamre et al, 1967;Oshiro et al, 1971). Later studies revealed that early in infection particle formation occurs predominantly at smoothwalled, tubulovesicular membranes located intermediately between the rough endoplasmic reticulum and the Golgi complex (ERGIC).…”
Section: A Viral Buddingmentioning
confidence: 99%